Sales Report Pada Momen Natal Tahun 2023 di Divisi Department Store PT. Trans Retail Indonesia - Kayla Malda Afrizza; Eko Cahyo Mayndarto; Wati Rosmawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Department Store is part of a supermarket that provides goods such as clothing, cosmetics, shoes, and accessories. This final project report aims to find out the sales report at the Christmas moment in 2023 in the department store division of PT Trans Retail Indonesia. This final project report uses primary data obtained through the system used by the PT Trans Retail Indonesia department store. Based on the results of data processing using vlookup and pivot, it shows that the sales results of the department store division at the Christmas moment in 2023 have decreased sales by 12.75% compared to the sales of the Christmas moment in 2022. With this it is very clear that the department store division's Christmas sales in 2023 did not reach the desired target.